Pelaksanaan Penilaian Ranah Afektif Menggunakan Google Form di Era New Normal - Marno, Marno; Tausih, Tsania Utsma (J-PAI: Jurnal Pendidikan Agama Islam, 2021)
This article aims to determine the planning, implementation, as well supporting and inhibiting factors in the affective assessment process using Google Form in the New Normal era in PAI SMKN 2 Magetan using a qualitative research approach with descriptive research type. 1) affective assessment planning consists of conductingÂ  KI / KD, determining the objective of the assessment, making a grid, selecting the type of instrument, and making scoring guidelines; 2) the implementation of affective assessments consisting of designing the instrument design, socializing the filling of the Google Form, asking students to complete the affective assessment, data processing and reporting the results; 3) the supporting factors for the implementation of affective assessment with Google Form consist of all parties who have tried their best, the government provides concessions to schools, students and teachers communicate actively, assessments are objective, comprehensive, economical, safety , and students' health is guaranteed. The inhibiting factors for affective assessment using Google Form consist of decreased student learning motivation, students experience internet network problems, teachers cannot monitor students directly.